Understanding disorganized attchment: theory and practice for working with children and adults - Shemmings, David 1951-
Disorganized attachment, the most extreme form of insecure attachment, can develop in a child when the person who is normally meant to protect them is a source of danger. This usually leads to 'fear without solution' and the effects can be lasting and damaging. This book is a comprehensive and accessible text on disorganized attachment. It outlines what it is, how it can be identified and the key causes, including neurological, biochemical and genetic explanations. Factors that contribute to disorganized attachment are covered including unresolved loss and trauma, and the behaviour of caregivers. The authors also discuss evidence-based interventions to help families and carers as well as how to work with adults to prevent or minimize its occurrence. To root the theory in practice and to illustrate real-life examples of disorganized attachment case vignettes are included. With an authoritative research base, this accessible text will be invaluable to practitioners and academics in the fields of social care, psychology, counselling and allied health professions as well as undergraduate and postgraduate students.